Unveiling APOL1 haplotypes in a predominantly African-American cohort of kidney transplant patients: a novel classification using probe-independent quantitative real-time PCR - Dogan, Murat; Watkins, Christine; Ingram, Holly; Moore, Nicholas; Rucker, Grace M.; Gower, Elizabeth G.; Eason, James D.; Bhalla, Anshul; Talwar, Manish; Nezakatgoo, Nosratollah; Eymard, Corey; Helmick, Ryan; et al. (Frontiers in Medicine, 2024)
Introduction: Apolipoprotein-L1 (APOL1) is a primate-specific protein component of highdensity lipoprotein (HDL). Two variants of APOL1 (G1 and G2), provide resistance to parasitic infections in African Americans but are also implicated in kidney-related diseases and transplant outcomes in recipients. This study aims to identify these risk variants using a novel probeindependent quantitative real-time PCR method in a high African American recipient cohort.Additionally, it aims to develop a new stratification approach based on haplotype-centric model.Methods: Genomic DNA was extracted from recipient PBMCs using SDS lysis buffer and proteinase K. Quantitative PCR assay with modified forward primers and a common reverse primer enabled us to identify single nucleotide polymorphisms (SNPs) and the 6-bp deletion quantitatively. Additionally, we used sanger sequencing to verify our QPCR findings.Results: Our novel probe-independent qPCR effectively distinguished homozygous wild-type, heterozygous SNPs/deletion, and homozygous SNPs/deletion, with at least 4-fold differences.High prevalence of APOL1 variants was observed (18% two-risk alleles, 34% one-risk allele) in our recipient cohort. Intriguingly, up to 12-month follow-up revealed no significant impact of recipient APOL1 variants on transplant outcomes. Ongoing research will encompass more time points and a larger patient cohort, allowing a comprehensive evaluation of G1/G2 variant subgroups categorized by new haplotype scores, enriching our understanding.Our cost-effective and rapid qPCR technique facilitates APOL1 genotyping within hours. Prospective and retrospective studies will enable comparisons with long-term allograft rejection, potentially predicting early/late-stage transplant outcomes based on haplotype evaluation in this diverse group of kidney transplant recipients.